Treatment Modalities in Recurrent Miscarriages without Diagnosis - Whitley, Kari A.; Ural, Serdar H. (Seminars in Reproductive Medicine, 2014)
Recurrent miscarriage is defined as the loss of three consecutive pregnancies before 20 weeks' gestational age. Patients are referred to subspecialists such as reproductive endocrinology or maternal fetal medicine to exclude the most common causes of recurrent miscarriage including autoimmune disorders, structural uterine pathology, metabolic derangements, hematologic conditions, and chromosomal abnormalities. Unfortunately, this extensive list of conditions accounts for less than 50% of patients affected by recurrent miscarriage, leaving the remaining 50% without answers. Multiple treatment modalities, including supplementation with progesterone, human chorionic gonadotropin, aspirin with and without heparin, and immune modulators have been tested for this large percentage of patients with very few answers. In fact, the only successful intervention addressed in the literature consists of supportive care at a dedicated recurrent miscarriage clinic. Without large randomized clinical trials, there is no evidence to support the use of supplemental medications in this patient population.
Keywords: recurrent miscarriage; unexplained miscarriage; miscarriage without diagnosis; treatment for recurrent miscarriage